Recent progress in the development of smart supercapacitors. Issue 2 (18th November 2022) - Xiong, Chuanyin; Wang, Tianxu; Zhao, Zhenyang; Ni, Yonghao
Abstract: Recently, with the continuous development of human society and the continuous innovation of technologies, the intelligence era has arrived. Various intelligent electronic devices continue to be developed, in which flexible wearable electronic devices are highly favored by people. To meet the requirements of the normal operation of intelligent devices, the key point lies in the development of new smart energy storage devices. Accordingly, smart supercapacitors have been widely focused on and studied by researchers recently with the introduction of intelligent functions, such as electrochromism, self‐healing, and shape memory, into supercapacitors to broaden their application fields and promote their smart development. This can meet not only people's energy needs but also people's diverse personality needs and make our life more convenient, fast, and more intelligent than ever. Therefore, it is very important to summarize related work on smart supercapacitors. Although researchers have performed much research on smart supercapacitors, there is still little literature summary on the related work of different smart supercapacitors. Accordingly, this paper mainly introduces the research progress on electrochromic, self‐healing, shape memory, and self‐charging smart supercapacitors in recent years and discusses the development prospects and challenges of smart supercapacitors. Abstract : Recently, with the continuous development of human society and the continuous innovation of technologies, the intelligence era has arrived. To meet the requirements of the normal operation of intelligent devices, the key point lies in the development of smart energy storage devices. Thereinto, smart supercapacitors have been of wide concern and studied by researchers. The research progress of smart supercapacitors in recent years, the development prospects, and the challenges of smart supercapacitors have been discussed in this review.